Mind-blowing modular origami the art of polyhedral paper folding - Loper, Byriah 1994- (Tokyo North Clarendon, VT Tuttle Publishing, 2016)
"Modular origami consists of multiple pieces of folded paper that are woven together into a single model. These composite forms range from starkly geometric models that are little more than paper representations of polyhedra, to bristling buckyballs reminiscent of sea urchins, to ornately embellished floral spheres. Each unit is held to the others strictly by the tension of the folded forms--a wonderful testimony to the remarkable hidden strength of paper. Modular origami models called "wire frames" comprise some of the most complex and exciting forms in origami today. Mind-blowing modular origami is the first book devoted primarily to the explanation of these intersecting, interlocking and interwoven creations. Assembling these pieces is always exciting and challenging, and the finished work is a visually stimulating piece that is well worth the effort"--Provided by publisher.
Preface -- Materials -- Tips and techniques -- Origami symbols -- Platonic solids -- Introduction to decorative modulars -- Introduction to wire frames
Keywords: Origami; Paper work; Polyhedra in art